2013
DOI: 10.1517/13543776.2013.780597
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and development of heat shock protein 90 inhibitors as anticancer agents: a review of patented potent geldanamycin derivatives

Abstract: Hsp90 inhibitors offer an effective therapeutic approach for treatment of cancer. To date, the clinical results of 17-AAG, IPI-493, and IPI-504 suggest that these GM derivatives could be used either alone or in combination with other marketed medications for the treatment of cancer patients. As there are not any marketed Hsp90 inhibitors, inhibiting Hsp90 chaperone function remains as a promising strategy that still requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…The benzoquinone ansamycin antibiotic geldanamycin has been shown to inhibit heat shock protein Hsp90 [1,2,3,4,5,6,7,8,9,10,11,12], which prevents stress-induced cellular damage [2], stabilizes various oncogenic kinases [1,7,9,10,12] and influences gene expression e.g. by up-regulating NF-κB [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzoquinone ansamycin antibiotic geldanamycin has been shown to inhibit heat shock protein Hsp90 [1,2,3,4,5,6,7,8,9,10,11,12], which prevents stress-induced cellular damage [2], stabilizes various oncogenic kinases [1,7,9,10,12] and influences gene expression e.g. by up-regulating NF-κB [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…by up-regulating NF-κB [13,14]. As Hsp90 expression is particularly high in cancer cells and is associated with tumor cell progression, invasion and formation of metastases, as well as development of drug resistance [2], geldanamycin and its analogues have been considered for treament of cancer [2,3,12,15,16,17,18,19]. Geldanamycin has been shown to induce apoptosis [1,5,6,8,9,10,15,20,21,22,23], an effect paralleled by altered gene expression, downregulation of Akt, p38 MAPK activation, mitochondrial depolarization, reactive oxygen species formation, decline of reduced glutathion, lipid peroxidation and caspase activation [5,9,15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…75 Despite the tendency for such electronrich hydroquinones towards rapid oxidation back to the corresponding quinone, it appears that the formation of the salt (hydrochloride in the case of IPI-504) stabilises the reduced form, although an in-depth study of this has, to the best of our knowledge, yet to be reported. The aqueous solubility of benzoquinone ansamycins increases significantly upon reduction to the hydroquinone (1-3 mg mL À1 for 17-AAG hydroquinone vs. 35 mg mL À1 for 17-AAG) 91 and this is even more marked upon salt formation, with solubilities in excess of 200 mg mL À1 typical for salts of 17-AAG hydroquinone. 91 Despite its discontinuation for the treatment of refractory gastrointestinal stromal tumours following a high mortality rate of patients in a clinical trial, 91 retaspimycin continues to perform in the clinic, with accumulating evidence of efficacy against multiple myeloma, lung cancer, and other solid tumours.…”
Section: -Allylamino-17-desmethoxygeldanamycinmentioning
confidence: 99%
“…91 Despite its discontinuation for the treatment of refractory gastrointestinal stromal tumours following a high mortality rate of patients in a clinical trial, 91 retaspimycin continues to perform in the clinic, with accumulating evidence of efficacy against multiple myeloma, lung cancer, and other solid tumours. 91 In addition to retaspimycin, other non-quinone-based Hsp90 inhibitors have been discovered through biosynthetic engineering and can exhibit increased binding affinities compared to geldanamycin and macbecin, although oxidation to the quinone is still a potential source of toxicity for the analogues. 92…”
Section: -Allylamino-17-desmethoxygeldanamycinmentioning
confidence: 99%
See 1 more Smart Citation